2021
DOI: 10.3390/antibiotics10060731
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Infection among Cirrhotic Patients with Variceal Bleeding

Abstract: Clostridioides difficile infection (CDI) stands as the leading cause of nosocomial infection with high morbidity and mortality rates, causing a major burden on the healthcare system. Driven by antibiotics, it usually affects older patients with chronic disease or immunosuppressed or oncologic management. Variceal bleeding secondary to cirrhosis requires antibiotics to prevent bacterial translocation, and thus patients become susceptible to CDI. We aimed to investigate the risk factors for CDI in cirrhotic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, the authors proposed a model of four predictors (age, days of admission, Charlson index, Child-Pugh score) to assess the risk of CDI in cirrhotic patients. Of note, in this study, cirrhotic patients with CDI had significantly higher costs compared with those without CDI [14].…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, the authors proposed a model of four predictors (age, days of admission, Charlson index, Child-Pugh score) to assess the risk of CDI in cirrhotic patients. Of note, in this study, cirrhotic patients with CDI had significantly higher costs compared with those without CDI [14].…”
mentioning
confidence: 52%
“…This retrospective cohort study included 367 cirrhotic patients with variceal bleeding, from which 25 patients were confirmed to have CDI. The authors reported that a higher age, longer hospital stay, higher level of urea, higher Charlson index, and the use of proton pump inhibitors were risk factors for CDI in cirrhotic patients [14]. Moreover, the authors confirmed that the MELD score was a predictor for mortality in cirrhotic patients with CDI.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In a further over six years study, CDI incidence was 11.8% in 388 cirrhotic patients, and notably, 30.8% of the cirrhotic patients received the antibiotic rifaximin to prevent HE [ 38 ]. In a study of patients with variceal bleeding, also conducted in Romania, the incidence of CDI was 6.8% between 2017 and 2019 [ 39 ]. Finally, in another hospital in China, the Infectious Diseases Department reported 26 cases of CDI in 526 cirrhotic inpatients over six months in 2015 (4.9%) [ 4 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Unnecessary antibiotic prescriptions increase the risk of adverse events at the individual level (such as Clostridium difficile infections and allergies [ 7 , 8 ]) and at the global level through antimicrobial resistance (AMR) development. AMR is highly prevalent in long-term care settings such as nursing homes, including resistance against commonly used antimicrobials to treat UTIs [ 4 , 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%